An algorithm to generate binary Gabidulin codes using SAGE - Gutierrez Garcia, Ismael; Zuleta Saldarriaga, Yesneri (Revista IEEE América Latina, 2015)
In this work we present a few algorithms to generate binary matrix code, specially binary Gabidulin code, using the mathematics software system SAGE.